PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS GAME FROGGY JUMPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SUMBER DAYA ALAM DI KELAS IV SD BIREUEN - Maulida; Khairunnisak; Lissa Zikriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' learning outcomes, teacher and student activities, and student responses through the implementation of the Problem-Based Learning (PBL) model assisted by the digital game media Froggy Jumps on the topic of Natural Resources in the 4th-grade class of SD IT Muhammadiyah Bireuen. The type of research used is Classroom Action Research (CAR) with 18 student subjects. The results showed a significant increase in all aspects measured, where teacher activity increased from 80.5% in cycle I to 95.8% in cycle II, and student activity increased from 68.4% to 92.1%. Furthermore, students' cognitive learning outcomes experienced a drastic improvement, with the class average score rising from 62.5 to 84.3 and the percentage of classical mastery increasing from 22.22% in cycle I to 88.89% in cycle II, alongside very positive student responses toward the use of this interactive media. In conclusion, the Problem-Based Learning model assisted by the Froggy Jumps digital game is effective in improving science learning outcomes (IPAS) regarding Natural Resources in elementary schools.